Analisis Kelayakan Potensi Ekowisata Hutan Mangrove di Dusun Matalalang Kecamatan Bontoharu Kepulauan Selayar. (Jurnal Hutan dan Masyarakat, 2020)
Abstract. The purpose of this research was to determine the feasibility value of the mangrove forest in Kepulauan Selayar district as an ecotourism object conducted for 2 months, from November 2017 to January 2018. The location was at Matalalang village, sub-district of Bontoharu, district of Kepulauan Selayar. The analysis method referred to the Guidelines of Operation Areas Analysis of Object and Natural Tourism Attraction (A DO-ODTWA) issued by Director General of Forest Protection and Natural Conservation (PHKA) 2003. The data analysis using Scoring according to the criteria in the guidelines. The attractiveness gets 6 because it is the main factor for a person doing tourism activities. The accessibility gets 5 because it is a crucial factor that supports visitors to carry out tourism activities. The accommodation and the supporting facilities/infrastructure get 3 because they are factors that support tourism activities. The calculation of each criterion using tabulation in which the numbers obtained from the respondents and researchers' assessment and the weighted values referred to the guidelines. The ecotourism feasibility assessment method used predetermined values for each criterion. The results of the ecotourism feasibility assessment shows that the Matalalang mangrove forest has a high number of classifications (2,160) and a feasibility index of 95.1% indicating that this area is potential and feasible to be developed as an ecotourism area.Keywords: Ecotourism, Forest, Feasibility Value, Mangrove
Keywords: Forest; Mangrove; Feasibility Value